IDENTIFIKASI TUMBUHAN BERBIJI (SPERMATOPHYTA) DI LINGKUNGAN KAMPUS UNIVERSITAS JEMBER - Isti Qomah; Sulifah Aprilya Hariani; Siti Murdiyah (BIOEDUKASI, 2015)
High diversity of plant in University of Jember caused a safe, healthy, and beautiful environment. Almost all the plant are Spermatophyta and have woody form. Spermatophyta is a group of plant that has seed as the main characteristic. The woody plant (arbo) is a plant that has stem from wood, big form, and various type. This research aimed to know the kinds of Spermatophyta around Jember University. This research was included as a qualitative descriptive research, which is carried to drawing, interpretating and describing data systematically, factual, and accurate about the facts and the characteristics of Spermatophyta around of University of Jember. The research design contained location the selection of research location, sample and picture taking, and plant identifying. The method of sample taking was cruise. There were 4.644 of Spermatophyta that already found, that contained 80 species and grouped on 32 families. These families were Anacardiaceae, Annonaceae, Apocynaceae, Araucariaceae, Arecaceae, Bignoniaceae, Burseraceae, Calophyllaceae, Casuarinaceae, Combretaceae, Cupressaceae, Ebenaceae, Euphorbiaceae, Fabaceae, Flacourtiaceae, Gnetaceae, Lamiaceae, Lauraceae, Lecythidaceae, Lythraceae, Magnoliaceae, Malvaceae, Meliaceae, Moraceae, Muntingiaceae, Myrtaceae, Oxalidaceae, Phyllanthaceae, Pinaceae, Rubiaceae, Sapindaceae, and Sapotaceae. Keywords: Identifying, Spermatophyta, University of Jember